Analysis of Clinical Characteristics, Treatment, and Prognostic Factors of 106 Breast Cancer Patients With Solitary Pulmonary Nodules - He, Lihong; Wang, Xiaorui; Liu, Xiaodong; Jia, Yongsheng; Zhao, Weipeng; Jia, Xiaochen; Zhu, Yuehong; Meng, Wenjing; Tong, Zhongsheng (Frontiers in Surgery, 2022)
Objective The clinical features of solitary pulmonary nodules (SPN) in breast cancer patients were retrospectively analyzed, and the clinical features of primary lung cancer (PLC) and metastatic pulmonary breast cancer (MBC) in breast cancer patients were compared, and the treatment plan, curative effect and influencing factors were analyzed. Methods The clinical data of 106 patients of SPN combined with breast cancer surgery in our hospital from January 2015 to June 2020 were analyzed. There were 65 patients of PLC and 41 patients of MBC. Record the characteristics of the primary breast cancer lesion in our patient, the interval between the initial diagnosis of breast cancer and the appearance of SPN, the previous treatment history of our patient, and the characteristics and surgical method of SPN. The survival status of all patients during the follow-up period was recorded. Results The onset age, interval, maximum nodule diameter, ER expression positive rate and radiotherapy history ratio of PLC patients were higher than those of MBC patients, and the lymph node positive rate and triple negative rate were lower than those of MBC patients (P < 0.05). Median survival was 51 months in patients with PLC and 37 months in patients with MBC. The 1, 3, and 5 year overall survival rates in patients with PLC were higher than those in patients with MBC (P < 0.05). Vascular tumor thrombus, SPN type and chemotherapy were all independent factors affecting the prognosis of patients with breast cancer combined with SPN (P < 0.05). Conclusion PLC patients and MBC patients have significant differences in pathological characteristics, like the onset age, interval, maximum nodule diameter, ER expression positive rate, radiotherapy history ratio, the lymph node positive rate, and triple negative rate. Septum, vascular tumor thrombus, SPN type, and chemotherapy are all independent factors that affect the curative effect of breast cancer patients with SPN. Based on the nature of SPN, it can provide reference for clinicians to decide the treatment plan, improve patients' quality of life and prolong their survival time.